A new snake from tile eastern andes of colombia (1946)
A small collection from northeastern Colombia recently sent for identification by my friend Hermano Nicéforo María of the Instituto de La Salle in Bogotá, contains a single specimen of a Leptotyphlops which I am unable to place in any of the described species.